Elucidating the impact of molecular packing and device architecture on the performance of nanostructured perylene diimide solar cells - Aluicio-Sarduy, Eduardo; Singh, Ranbir R.; Kan, Zhipeng; Ye, Tengling; Baidak, Aliaksandr; Calloni, Alberto; Berti, Giulia; Duò, Lamberto; Iosifidis, Agathaggelos; Beaupré, Serge; Leclerc, Mario; Butt, Hans Jürgen; et al. (My University, 2015)
The performance of organic photovoltaic devices (OPV) with nanostructured polymer:perylene diimide (PDI) photoactive layers approaches the levels of the corresponding polymer:fullerene systems. Nevertheless, a coherent understanding of the difficulty for PDI-based OPV devices to deliver high power conversion efficiencies remains elusive. Here we perform a comparative study of a set of four different polymer:PDI OPV model systems. The different device performances observed are attributed to differences in the nanostructural motif of these composites, as determined by wide-angle X-ray scattering (WAXS) measurements. Long-range structural order in the PDI domain dictates (i) the stabilization energy and (ii) the concentration of the PDI excimers in the composites. The quenching of the PDI excimer photoluminescence (PL) is found to be insensitive to the former, but it depends on the latter. High PL quenching occurs for the low concentration of PDI excimers that are formed in PDI columns with a length comparable to the PDI excimer diffusion length. The stabilization of the PDI excimer state increases as the long-range order in the PDI domains improves. The structural order of the PDI domains primarily affects charge transport. Electron mobility reduces as the size of the PDI domain increases, suggesting that well-ordered PDI domains suffer from poor electronic connectivity. WAXS further reveals the presence of additional intermolecular PDI interactions, other than the direct face-to-face intermolecular coupling, that introduce a substantial energetic disorder in the polymer:PDI composites. Conventional device architectures with hole-collecting ITO/PEDOT:PSS bottom electrodes are compared with inverted device architectures bearing bottom electron-collecting electrodes of ITO/ZnO. In all cases the ZnO-functionalized devices surpass the performance of the conventional device analogues. X-ray photoelectron spectroscopy explains that in PEDOT:PSS-functionalized devices, the PDI component preferentially segregates closer to the hydrophilic PEDOT:PSS electrode, thus impeding the efficient charge extraction and limiting device photocurrent.
Keywords: Charge extraction; Non-fullerene acceptors; Organic photovoltaics; Perylene diimide; Vertical phase separation